Developing Students’ Intercultural Competence among Moroccan EFL students: Focus on raising their Cross-cultural Awareness - Benattabou, Driss (International Journal of Language and Literary Studies, 2020)
The goal of this paper is to consider alternative ways to incorporate an intercultural communication course as an integral part of the curriculum designed for Moroccan learners of EFL. Some aspects of what comes to be dubbed as ‘deep culture’ should find room in the contents of the EFL course so as to alert Moroccan learners about the potential intercultural barriers they are far more likely to face. It is proposed that for an effective intercultural communication to take place, the English course should help foreign language learners explicitly understand what target linguistic forms might be and how their meanings may differ across cultures. The analysis of some instances of intercultural misunderstandings may surely give more credence to the vital importance of implementing a multicultural approach to education. This paper offers some teaching strategies to assist Moroccan learners of EFL overcome these intercultural barriers.